Language of Desire: A Methodological Contribution to Overcoming Gender Violence. (2nd August 2021) - Melgar Alcantud, Patricia; Puigvert, Lidia; Rios, Oriol; Duque, Elena
Previous research has generally found that providing specific research evidence about concrete improvements in the development of field work promotes the achievement of social impact during the research process itself (Aiello et al., 2021 ). This result opens as a prospective for further research to specify which scientific evidences can promote this impact in the different research topics, as well as the methodological aspects that will facilitate it. In research on gender violence, some of these evidences have already been identified—for example, the mirage of upward mobility (Oliver, 2010-2012 ). However, the methodological aspects that will determine, when exposing such evidence, the social impact obtained during the research process have not been analyzed. In this sense, in the FREE TEEN DESIRE project, sharing this evidence with the participants using the language of desire has promoted transformations. This language of desire must be incorporated from its reality, being the result of a construction between the researcher and the participants. Its incorporation is enhanced if it is done in the context of Dialogic Feminist Gatherings (DFG). And, throughout the process, the researcher must adopt a role in which, among other things, she or he makes visible any attitude linked to violence when it becomes unattractive, as well as making visible the language of desire that is being constructed with respect to egalitarian relationships. The social impact of this research methodology was evidenced by the fact that after participating in DFG on the mirage of upward mobility, the girls' intention to have a sporadic relationship with a boy with violent attitudes decreased (Puigvert, 2016 ).